Antibiotic resistance and virulence genes of Vibrio alginolyticus from Asian seabass in the East Coast of Peninsular Malaysia - Ain-Auzureen, Mat Zin; Mohamed, Maizan; Peng, Tan Li; Ghazali, Mohd Faizal; Shean, Choong Siew; Mardhiah, Kamaruddin; Musa, Najiah; Mohamad, Nora Faten Afifah; Hian, Chai Min; Hamdan, Ruhil Hayati (ResearchersLinks Ltd, 2024)
Vibrio alginolyticus caused vibriosis and contributed to a major problem in seabass farming. This study aims to determine the antibiotic resistance and virulence genes of V. alginolyticus isolates from Asian seabass in the East Coast of Peninsular Malaysia. A total of 180 Asian seabass was dissected and a loopful of kidney and liver samples were inoculated on thiosulphate-citrate bile-salt sucrose (TCBS) agar and CHROMagarTM Vibrio. Polymerase chain reaction (PCR) was used to identify the isolates and detect the twelve virulence genes associated with V. alginolyticus. Antibiotic resistance tests were conducted using 17 antibiotics. The difference in index scores between locations was tested using one-way ANOVA, while the index scores between (multidrug resistance index) MARi and multi-virulence gene indexes (MVGi) were compared using the Mann-Whitney test. Total of 26 (7.2%) isolates out of 360 organ samples were determined as V. alginolyticus. The observation of external lesions was haemorrhagic eyes, pale skin, detachable scales, pale liver and enlarged spleen. Twenty-six isolates of V. alginolyticus were containing chiA (100%) and 96% of colA genes. None of the isolates possess hlyA, toxRVH, toxRVC, and trh-tdh genes. MVGi were varying from 0.16 to 0.33. In addition, 18 antibiotic resistance patterns were identified, and the MARi ranged from 0.05 to 1. It is alarming that seven out of 12 isolates from Sungai Besut, Terengganu were resistant to all antibiotics tested. The statistical analysis revealed that the mean MARi in Besut, Terengganu was significantly higher than in other locations (P=0.032). Additionally, the index score between MARi and MVGi was found to be significantly different (P=0.013), indicating a possible relationship between the two variables. The outcome of this study may be helpful in elucidating V. alginolyticus pathogenicity and evaluating antibiotics misuse for the development of sustainable disease control methods.